Courting public favour: the Boy Scout movement and the accident of internationalism, 1907−291. Issue 241 (10th September 2014) - Johnston, Scott
Abstract This article explores how the Boy Scout movement moved from an inward looking and decidedly militaristic programme to one which embraced liberal internationalism following the First World War. It argues that the Boy Scouts' wholehearted embrace of internationalism was not inevitable; in fact it was a complex and inconsistent transition, and the result of unintentional circumstances. Furthermore, internationalism did not replace but merely supplemented the movement's older aims of organizational autonomy and the promotion of empire. During the inter‐war period, these competing motives informed and strained the Boy Scouts' interactions with the public and with other internationalist organizations such as the League of Nations and the League of Nations Union.